SANG AMURWABUMI SEBAGAI SIMBOL LEGITIMASI SULTAN HAMENGKU BUWANA X - S. Supriyanto (Institut Seni Indonesia Surakarta, 2015)
Beksan Bedhaya, refers to its understanding, belongs to traditional theater, a valuable form of art that is stillconserved in the palace including Surakarta as well as Yogyakarta Palace. Traditionally, dance Bedhaya isdanced in group by nine young female dancers. Dance Bedhaya, with its sacred, takes a story based on mythor legend that thematically contains of philosophic and sociolinguistic meanings as well as bringing ethic andmoral values, and also actual life teachings of a certain age. The spiritual aspects, hereditary, have becomea basic concept that bases the aesthetic choreographic concept of dance Bedhaya. All process of danceBedhaya and its dancers’ names related to the symbol from the beginning until the end represent the humanbirth, life, and death. The process tells about purwa (beginning/birth), madya (life), and wasana (the end) ofhuman life. The understanding of content and meaning in dance Bedhaya Amurwabumi contains ritual valuesas the forms of glory and legitimacy along with other things. Dance Bedhaya also has a function to keep theunity between Sultan and his kawula (people) that is found in the concept of manunggaling kawula alit orcuriga manjing warangka, warangka manjing curiga.Keywords: Bedhaya, Sang Amujrwabumi